Implementation of augmented reality-assisted learning media on three-dimensional shapes - Surya Amami Pramuditya; Sri Pitriayana; Toto Subroto; Risnina Wafiqoh (Universitas Hamzanwadi, 2022)
This research is motivated by the low understanding of students in studying the object of geometry study. The media that had previously been used in the form of a spatial framework made of bamboo or iron turned out to take up quite a lot of space and was not practical to carry in large quantities. Therefore, efficient and practical media are needed to help visualize concrete objects in learning. This research aims to implement Augmented Reality (AR)-assisted learning media on the material of three-dimensional shapes. This study uses an explanatory qualitative method. The participant in this study was one student from one of the junior high schools in the Cirebon Regency. Data collection techniques used are through interviews and documentation. The analysis technique consists of three stages: data reduction, data presentation, and concluding. The results showed that the AR application could make it easier for the student to understand the material and solve the problem of three-dimensional shapes. However, the student still has a little difficulty using the application and is a little confused when identifying the parts of the cube because the image of the shape raised by the application is still not clear. This research implies that AR applications can make students' spatial abilities better.